Increasing capacity to address the physical health needs of patients in a mental health and addictions hospital. Issue 4 (16th March 2022) - Kalia, Kamini; Ling, Sara; Moghabghab, Rola; Branton, Sarah; Islam, Faisal; Saiva, Anika; Kim, Jayoung; Sliekers, Stephanie; Harren, Dan; Robins, Amanda
Abstract: Purpose: This paper describes the strategy and outcomes of a quality improvement initiative focused on building the capacity of nurses at a mental health and addictions teaching hospital to provide an improved standard of physical health care. Education was provided via a series of e‐learning modules and interactive workshops. To reinforce the education and enhance practice change, improvements were made to electronic documentation templates and organizational standards. Further, the organization provided increased access to physical health equipment, a mobile application to support assessments and a reference card for lanyards. Conclusions: Nurses identified increased confidence in performing physical assessments, and documentation improved with standards and automated forced functionality in the electronic health record. Ultimately, the organization successfully implemented a multifaceted strategy to improve physical healthcare services for people with mental health and substance use concerns. Practice Implications: Organizational investment can lead to sustainable changes in nursing confidence and increased physical health assessment completion.